2014
DOI: 10.1063/1.4885137
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory approach to gold-ligand interactions: Separating true effects from artifacts

Abstract: Donor-acceptor interactions are notoriously difficult and unpredictable for conventional density functional theory (DFT) methodologies. This work presents a reliable computational treatment of gold-ligand interactions of the donor-acceptor type within DFT. These interactions require a proper account of the ionization potential of the electron donor and electron affinity of the electron acceptor. This is accomplished in the Generalized Kohn Sham framework that allows one to relate these properties to the fronti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 89 publications
(92 reference statements)
0
17
0
Order By: Relevance
“…Increasing the total fraction of HF exchange too much may distort the balance in error compensation between correlation and exchange functionals, resulting in the incorrect behavior of the energy contributions. 89,90 We show this by plotting the first-order, E (1) = E elst + E exch , and dispersion, E (2) disp,tot = E (2) exch−disp + E (2) disp energies, for the Ar. .…”
Section: A24 and Di6-04 Test Resultsmentioning
confidence: 99%
“…Increasing the total fraction of HF exchange too much may distort the balance in error compensation between correlation and exchange functionals, resulting in the incorrect behavior of the energy contributions. 89,90 We show this by plotting the first-order, E (1) = E elst + E exch , and dispersion, E (2) disp,tot = E (2) exch−disp + E (2) disp energies, for the Ar. .…”
Section: A24 and Di6-04 Test Resultsmentioning
confidence: 99%
“…This is not surprising: similar observations were made by Refaely-Abramson et al 38 and confirmed in additional studies. 39,92,93 In order to provide an explanation for the origin of this behavior, orbital plots of the five highest-occupied orbitals, as well as the LUMO, are shown in Fig. 2b.…”
Section: A Gas Phase Of Quinacridonementioning
confidence: 99%
“…These data can be obtained free of charge from The Cambridge Crystallographic Data Centre via www.ccdc.cam.ac.uk/data_ request/cif. (19) C11-S11-Au1 104.6(3) C31-S31-Au2 103.2(3) Au1-S2-C1-S1 −3.6(4) Au1-S1-C1-S2…”
Section: X-ray Crystallographymentioning
confidence: 99%
“…12,13 Finally, over the last decade the role of gold thiolates in the formation and stabilization of nanoparticles has also been a matter of extensive studies. 12,[14][15][16][17][18][19] Gold bisthiolato complexes constitute an interesting group of thiolates. In this class of compounds the Au(I) centre may be incorporated either in the cationic or anionic units of the [Au(SR) 2 ] +/− type depending on the nature of the ligand.…”
Section: Introductionmentioning
confidence: 99%